If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + -6u = u Solving 35 + -6u = u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. 35 + -6u + -1u = u + -1u Combine like terms: -6u + -1u = -7u 35 + -7u = u + -1u Combine like terms: u + -1u = 0 35 + -7u = 0 Add '-35' to each side of the equation. 35 + -35 + -7u = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -7u = 0 + -35 -7u = 0 + -35 Combine like terms: 0 + -35 = -35 -7u = -35 Divide each side by '-7'. u = 5 Simplifying u = 5
| 4(3x+11)=2.6(16+4x) | | -f(x)=x^2+5x-2 | | 4(3x+11)=2.7(16+4x) | | 4(3x+11)=0(16+4x) | | 4(3x+11)=2.5(16+4x) | | 9-7v-1.1-8v= | | y=-x^2+5x+14 | | 2m+8-7m=23 | | .0833(156x-17)=5(18+12x) | | 9a-20= | | Cos^2x-5sinx-5=0 | | f(x)=-163+200x | | 12-w=52 | | 10x-14.30=26.00 | | 3(2m+4)=6m+12 | | H+28.80=86.40 | | x(.97)=275 | | H(x)=6x+2 | | H+1=28.80 | | (-2x^3+x)+(3x-6)= | | 3y+6=5y+2 | | 2-m/2 | | 275=x-(3/100) | | (45x-15)/5 | | 3x^2-14x+18=3 | | 9x+2+17x+1=13x-18+17x+1 | | 2t+10=4t-50 | | -8x+-21= | | 4(3x+11)=2.8(16+4x) | | 2-m/21 | | 8x+-21= | | -2x-6=6+2x |